RIO Country Report 2016: Cyprus - Theocharous, Antonis L.; Gampfer, Robert; Robledo, Bottcher Nicolas (My University, 2017)
This publication is a Science for Policy report by the Joint Research Centre (JRC), the European Commission’s science and knowledge service. It aims to provide evidence-based scientific support to the European policymaking process. The scientific output expressed does not imply nor prejudge policy positions of the European Commission. Neither the European Commission nor any person acting on behalf of the Commission is responsible for the use that might be made of this publication.
Keywords: Innovation and growth; Information society; Science for policy